(untitled) - Ackert, Patricia (Boston, MA, 2005)
Through wonderful readings and carefully designed activities, this best-selling series helps students develop reading skills and systematically increase their active vocabulary. Learners develop useful and relevant vocabulary while exploring and expanding critical thinking skills.
Keywords: English language,Readers; Textbooks for foreign speakers